(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2019)
Art Deco emerged from the change of thinking ways of a group of people who one of them backed from the establishment of the economy. In Surakarta, there are areas that get influence Art Deco style, among others: Baluwarti, Laweyan, and Kauman. The problem is the absorption and adaptation of elements of Javanese culture and other culture that produce different art deco typology in each object of study. This study aims to compare the absorption and adaptation of elements of Javanese culture and other culture that produces different art deco typologies in three different areas in Surakarta.With different backgrounds, the absorption and adaptation of Art Deco style in residential houses in each region is different. But the common thread is the absorption of several styles, namely: Java, Art Deco, Art Nouveau, Middle East, and China which finally created the eclectic Art Deco style.